Survey of the mechanical and physical behaviors of yttria-stabilized zirconia from multiple dental laboratoriesWhy Is This Important? - Yifeng Liao, PhD; Max Gruber, BSE; Henry Lukic, BSE; Jim McLees, CDT; Si Chen, PhD; Alan Boghosian, DDS; Spiro Megremis, MS, PhD (JADA Foundational Science)
Background: When selecting zirconia for a dental restoration, laboratory prescriptions often refer to high strength and high translucency. In this survey, zirconia specimens were ordered from various dental laboratories for posterior (high strength) and anterior (high translucency) clinical indications. The specimens were then tested and evaluated for their mechanical and physical behaviors. Methods: In a double-blinded manner, 9 laboratories provided 32 specimens from 17 different zirconia blanks, which were tested in the American Dental Association laboratory. Flexural strength tests were performed on standard specimens, and fracture surfaces were examined using both optical and scanning electron microscopy. Chemical composition, Vickers hardness, and absolute transmittance measurements were also performed. Results: A large scatter in the strength values was observed. The zirconia intended for posterior applications displayed strengths (SD) from 195 through 783 MPa (490 [183] MPa), which overlapped greatly with the strengths (SD) of the zirconia intended for anterior applications, 320 through 768 MPa (581 [136] MPa). However, when the strength values were recalculated on the basis of yttria content, the strengths (SD) were 584 (158) MPa for 3 mol% yttria and 373 (104) MPa for 5 mol% yttria. Conclusions: When a prescription was given to dental laboratories to request zirconia on the basis of clinical requirements, there was a large scatter and no consistency in the resulting strength values partly because of mixed use of 3 mol% and 5 mol% yttria zirconia. The 3 mol% materials had much higher strength when the strength values were grouped according to yttria content. Strength was also highly dependent on processing and finishing at the dental laboratories.